DEVELOPING AN INTEGRATED MODEL OF GRADUATE EMPLOYABILITY IN MALAYSIA: A SYSTEMATIC LITERATURE REVIEW - Zaherawati Zakaria; Nazni Noordin; Mohd Zool Hilmie Mohamed Sawal; Nurul Amira Azmi (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Graduate employability in Malaysia has become a significant issue as many graduates enter the competitive job market. This systematic literature review aims to create an integrated model to enhance the employability of Malaysian graduates by synthesizing existing information on the key determinants that impact employability outcomes. A comprehensive search of academic, government, and industry papers was conducted, with an emphasis on research published between 2000 and 2024. The review highlights many important factors of graduate employability, including the quality and relevance of higher education, skills mismatch, economic conditions, government policies, and the importance of soft skills and industry collaboration. The proposed model emphasizes the role of internal elements (education, skills, personal characteristics) and external factors (economic conditions, labor market demands, government efforts) in shaping graduate employability in Malaysia. The findings highlight the importance of a comprehensive and coordinated approach that combines educational institutions, industry, and policymakers to improve graduate outcomes. This research provides important insights for improving graduate employability strategies and practical recommendations for stakeholders to bridge the employability gap in the Malaysian workforce.